About Demarcation and Synthesis between the Political Economy and the Economics - Beev, Ivaylo (Research Papers, 2018)
By the end of the 19th century, the economists began to define political economy with a new term - "Economics". In parallel, start a process to upgrade of the content of the new term. This results in a "new" science for the "economy", ie. it becomes obvious that in the present day the synonymization of "political economy" with "economics" is not legitimate.In this study, the author does not intend to make a full distinction between political economy and economics – just to mark another significant dividing line between these two economics studies and to answer the question whether and under what conditions one can speak of a synthesis between them.
Keywords: Political economy; Economics; Methodological individualism; Economic determinism